COMPARATIVE STUDIES ON INTESTINAL PHOSPHATASES IN FISHES - BALASUBRAMANIAN, M. P.; PALIANICHAMY, S.; ARUNACHALAM, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
Biochemical properties of intestinal phosphatases were studied in the fishes Oreochromis mossanbicus (Omnivorous), Labeo rohita (Herbivorous) and Channa striata (Carnivorous). The pH optimum for phosphatases was found to differ in these fishes. Acid phosphatase activity was higher than that of alkaline phosphatase in O. mossambicus, whereas in L. rohita and C striata, the activity of both acid and alkaline phosphatases were more or less similar. Effect of substrate concentrations of the intestinal phosphatases at their respective optimum pH revealed that the V max and Kim varied with fishes. Influence of the chemicals on phosphatases varied with fishes.